2014
DOI: 10.1021/mz500122v
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of Soft Foam Solids: Interplay of Visco- and Plasto-elasticity

Abstract: Fracture mechanical properties of a very soft solidified foam of polyethylene with Young's modulus about 1 MPa are studied by changing stretching velocity in a wide range, by using sheets of the material in order to suppress finite-size effects. Unexpectedly, we find that the fracture can be described well by linear elastic fracture mechanics for a given fracture rate in the wide range. This allows a direct determination of velocity-dependent fracture energy of the soft foam. As a result, we find that the frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Since we have established the same reasoning for Eq. (3) in Ref [26]. for soft foam sheets of polyethylene, the present result suggests a certain degree of universality of Eq.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Since we have established the same reasoning for Eq. (3) in Ref [26]. for soft foam sheets of polyethylene, the present result suggests a certain degree of universality of Eq.…”
supporting
confidence: 72%
“…were measured with a hand-made setup, which was used in our previous study [26]. This Fracture mechanical measurements are performed with the same setup but with introducing a macroscopic line crack with a sharp knife at the center of the sample (see Fig.…”
Section: B Mechanical Measurementmentioning
confidence: 99%
“…The material of sheet samples is Kent paper (high quality paper with fine texture mainly used for drafting) of thickness h ( h ≃ 0.2–0.3 mm), whose Young’s modulus E is measured to be in the range E ≃ 2.45–3.27 GPa (with the standard deviations less than ≃5%). We measured force as a function of extension by a force gauge (FGP-0.2, NIDEC-Shimpo) mounted on an automatic slider system (EZSM6D040, Oriental Motor) as in the previous studies on fracture 17 18 19 . The extension speed is fixed to a slow speed (0.5 mm/s) to remove dynamic effects.…”
Section: Methodsmentioning
confidence: 99%
“…[10] In the case of a polyethylene foam sheet whose typical foam size is of millimeter-scale, it was found that the flow of polymer happens only on the scale of foam at the crack tip. [16] The structural size-effect is also verified with numerical simulations; it has been shown that, by changing the mesh size of a network model for elastic sheets, the failure stress of a sheet with a crack can be tuned. [17] For crack propagation, in a numerical simulation [18] and a theoretical model, [12] it is confirmed that mesh size affects crack velocities.…”
Section: Introductionmentioning
confidence: 81%
“…However, the direct measurement for matrix materials is impossible as explained above while these matrix properties are reflected in bulk viscoelastic measurements to some extent, which is similar for the three samples. In addition, the most important length scale at crack tips is the pore size; for example, the crack opening distance, the size of yielding zone near the crack tips, [28] the size of the region in which viscous flow occurs, [16] and the radius of curvature at a crack tip are all governed by the pore size. These are the reasons we consider the pore size should be physically most important for considering crack propagation in the present porous polymers.…”
Section: Methodsmentioning
confidence: 99%